Melacak Nasib Citra Daerah: Analisis Keterangan Akhir Pada Jadwal Retensi Arsip - Rakhmawati, Rina; Jannah, Syahida Raihana; Azizah, Rintis Rindang (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2024)
Background: Records retention schedule is an instrument in records appraisal phase. One of component in the schedule represents the final fate of records in an organization, that is “keterangan”. Theoretically, the number of documents that are justified as permanent records should be not be greater than the documents that should be destroyed.Objective: This paper aims to describe the results of mapping and analysis of the final decision components on the records retention schedules. By mapping the final decision components on the schedule, we will know the comparative percentages of records that should be permanent than should be destroyed. The author then analyzed the causes and impacts for records management in creator institutions.Methods: The research conducted is a qualitative study with a content analysis approach combined with in-depth interviews. The author uses the provincial government of the Special Region of Yogyakarta as the research case.Results: There were variations were found in the final decision components which are recommendations for the execution of records disposal, namely destroyed, permanent, re-appraisal, and others. The number of record series recommended to be destroyed is greater than the number of record series recommended to be permanent. However, this comparison is still not in line with the quantity of archives that are made permanent according to various experts, which is in the range of 1% to 10%. Those phenomena were suspected to have emerged as a result of the concerns of the creators over the risks that must be weighted if the document is immediately declared as destroyed and/or permanent.Conclusion: The practical implication is that it can provide an illustration that there is still an asynchronization in understanding the function of appraisal and disposal, especially in understanding retention schedule and records values as an instrument. Some future researches need to explore how arsiparis making a disposal decision so that we can understand records urgency for their creators and public.